Pengaruh Metode Blended Learning dalam Peningkatan Pengetahuan Sumber Daya Manusia Kesehatan di Puskesmas Sulawesi Utara - Rima Lolong; Viktory Nicodemus Joufree Rotty; Henny Nikolin Tambingon (Neolectura, 2022)
Blended learning is a blend of several types of distance and face-to-face learning. It is claimed that blended learning increases students' knowledge. Therefore, it is necessary to implement blended learning in health human resource (HR) training. The objective of this study was to examine the impact of blended learning on training on the increase of human resource knowledge at Puskesmas in North Sulawesi. This is a quasi-experimental study with a one-group pre-posttest design. This study was conducted between 5 and 10 September 2022 at the Regional Technical Implementation Unit (UPTD) of the Health Training Center (Bapelkes) of the Regional Health Office (Dinkesda) of North Sulawesi Province. This study surveyed 30 Health Human Resources, specifically the Rapid Action Team for Conquering Outbreaks and Outbreaks at Puskesmas. This study's dependent variable is the level of knowledge. The tool utilized is a questionnaire. In this study, univariate and bivariate data analysis are employed. The results of this investigation suggest that the minimum, maximum, and mean values have all increased. The minimum value grew by 48.50 points, the maximum value by 30 points, and the average value by 33.33 points. The results of the t-test reveal a t-value of 20.0478 and a p-value of 0.0001 (p0.05). These values represent a difference in knowledge between before and after receiving blended learning training. The outcome of this study is that training with the blended learning method has an effect on the trainees' knowledge. integrated learning; human resources in health; training; knowledge.